Ahmad Rūmī Akhisārī’s Unknown Book Iʿtikād Risālesi and Some Analysis’s about his Denominational Belonging with Reference to his Opinions Related to Pain Point of Importance of learning of Positive-Transferred Sciences - Transcription and Evaluation - Ali Durmuş (İslam Tetkikleri Dergisi)
This study aims to transcribe and evaluate a book entitled I’tikād Risālesi, which remained unknown until recently and is penned by Ahmad Rūmī Akhisārī (d. 1041/1631-32). The author is one of the leaders of Qādī-zādelis Movement that emerged for some religious and political reasons during the Ottoman Empire in the 17th century. I’tikād Risālesi, is composed of a few pages that highlight Akhisārī’s opinions regarding the importance of learning and teaching positive sciences (‘ulūm al-‘akliyye) and transferred sciences (‘ulūm al-nakliyye). Akhisārī penned the book to express own opinions about education of positive and transferred sciences and to fill the research gap in this field. Moreover, the our study intends to reveal and evaluate Akhisārī’s opinions related to such forms of sciences with reference to this book. İn addition, the study aims to determine his attitude about the science of Kalam by applying the his concepts to other books of the same author. Thus, the study evaluates and analyzes denominational belonging of the author. Vievs about sciences of Akhisārī who one of the leaders of aforesaid movement which is both accused by Salafism and asserted its showing up based on Birgivī (d. 981/1573) only is having feature that shake to these claims. Therefore, the study both fills these research gaps about these claims and makes aforesaid book which is never known until recently available to researchers who is researcing in this branch.